On the [p, q]-order of analytic solutions of linear differential equations in the unit disc - Belaıdi, Benharrat (Novi Sad J. Math, 2012)
In this paper, we study the growth of analytic solutions of homogeneous linear differential equations in which the coefficients are analytic functions of [p, q]− order in the unit disc.